2005
DOI: 10.1007/s11916-005-0038-z
|View full text |Cite
|
Sign up to set email alerts
|

Functional brain imaging in hemicrania continua: Implications for nosology and pathophysiology

Abstract: Hemicrania continua is a strictly unilateral, continuous headache of mild to moderate intensity, with superimposed exacerbations of moderate to severe intensity that are accompanied by trigeminal autonomic features and migrainous symptoms. The syndrome is exquisitely responsive to indomethacin. Its clinical phenotype overlaps with that of the trigeminal autonomic cephalalgias and migraine, in which the hypothalamus and the brain stem, respectively, have been postulated to play central pathophysiologic roles. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 77 publications
1
16
0
Order By: Relevance
“…Summary of current functional imaging studies in different forms of trigeminal autonomic headache syndromes [22, 87, 88, 90–92, 9597]…”
Section: Neuroimaging In Trigeminal Autonomic Cephalalgiasmentioning
confidence: 99%
“…Summary of current functional imaging studies in different forms of trigeminal autonomic headache syndromes [22, 87, 88, 90–92, 9597]…”
Section: Neuroimaging In Trigeminal Autonomic Cephalalgiasmentioning
confidence: 99%
“…The clinical manifestation of HC overlaps with that of others trigeminal autonomic headaches and migraine in which activations in the hypothalamus and dorsal rostral pons, respectively, have been postulated to play important pathophysiologic roles 13–17 …”
mentioning
confidence: 99%
“…The direct inhibition of trigeminocervical complex or the modulations of neurons that regulate sensory input have been proposed as possible mechanisms for topiramate's preventive action in these headache types. 11,12 According to our findings, topiramate would be an interesting alternative option in patients with HC who have contraindication or intolerance to indomethacin. However, the result shown by the patient in the present study needs to be confirmed by larger controlled clinical trials and other case series.…”
Section: Discussionmentioning
confidence: 70%